2020
DOI: 10.3390/su12229345
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and Influencing Factors of Social Virtual Reality in the Urban Elderly

Abstract: In the stage of aging society and population aging, the social needs of the elderly are widely discussed by researchers. Especially driven by the demand of tele-medical treatment and tele-rehabilitation therapy, it is vital for the elderly to integrate into virtual communities by combining social virtual reality (VR) with different medical services and entertainment needs. In addition, affected by the COVID-19 epidemic, it is more difficult for people to have face-to-face contacts. With more remote consultatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
0
21
2
Order By: Relevance
“…The possibilities of VR to alleviate loneliness and social isolation have been studied in [ 159 , 160 ] and the video-conference interaction program in [ 161 ]. The results of these studies were positive, but engaging family members may partly explain the decline in loneliness and depression to the programs, instead of other more distant social contacts or strangers.…”
Section: Proposed Wearable-based Monitoring and Management Solutionsmentioning
confidence: 99%
“…The possibilities of VR to alleviate loneliness and social isolation have been studied in [ 159 , 160 ] and the video-conference interaction program in [ 161 ]. The results of these studies were positive, but engaging family members may partly explain the decline in loneliness and depression to the programs, instead of other more distant social contacts or strangers.…”
Section: Proposed Wearable-based Monitoring and Management Solutionsmentioning
confidence: 99%
“…Based on many previous studies, several differences were observed in the perceptions and attitudes of urban and rural teachers, toward the use of technology-based learning media (Kim and Jung, 2010;Siaw et al, 2018;Niens et al, 2021). Some of them also showed the factors influencing these teachers' utilization intentions, with the integration of IWB in poor rural and remote areas found to be limited (Setyono and Cahyo, 2017;Siaw et al, 2018;Shao and Lee, 2020). This verifies that a subsequent report is still needed to obtain a deeper understanding of the models and methods responsible for the factors influencing teachers toward using IWB in remote and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, XR telehealth has expanded to a wide variety of remote health care applications in AR telesurgery and telesupervision, MR training and simulations, VR telemental health, and telemonitoring of fully remote interventions and specialized medical equipment with VR/AR [13,38,39]. Similar growth occurred in consumer markets with reported use of entertainment VR apps and video games for therapeutic purposes such as mental wellness, identity exploration, healthy aging, and social anxiety [40][41][42].…”
Section: Xr For Telehealth Before Covid-19mentioning
confidence: 96%